Does the social platform established by MMORPGs build social and psychological capital?. (April 2022) - Hsu, Chiu-Ping; Chang, Chia-Wen
Abstract: Online social capital is a key topic, and numerous studies have examined various outcome variables of online social capital in game research. However, few studies have explored the relationship between online social capital and psychological capital in game research. Psychological capital is a valuable asset for individuals coping with psychological challenges associated with the COVID-19 pandemic. Thus, this study primarily explores the effect of online social capital (bonding and bridging) on the four dimensions of psychological capital (hope, optimism, self-efficacy, and resilience). Moreover, this study explores the effect of learning and online and offline social interactions on online social capital. An online questionnaire survey was administered to a sample of 548 massively multiplayer online role-playing games (MMORPGs) players. Structural equation modeling was applied to test the proposed model, and it reveals that all hypotheses are supported. The results indicate that learning and online and offline social interactions help players to establish online social capital, which in turn improves their psychological capital. Highlights: A sample of MMORPG players was surveyed during the pandemic. Online social capital has a positive impact on psychological capital. Learning has a positive impact on online social capital. Online social interaction has a positive impact on online social capital. Offline social interaction has a positive impact on online social capital.